GENERAL FACTORS AND ITS ELEMENTS AFFECTING PARTICIPANTS OF EXTERNAL ECONOMIC ACTIVITY ON RISK LEVELS, ALGORITHM BASED ON THREE SIGMA RULE OF RISK DETERMINATION (IN THE EXAMPLE OF UZBEKISTAN) (American Journal of Pedagogical and Educational Research, 2023)
In the article, the reasons for the introduction of the "Risk Management" system to the customs authorities, the necessary elements that ensure the operation of the "Risk Management" system and their characteristics, the factors affecting the risk and their importance.Processes of collecting and processing information necessary to identify risks and determine their levels, identify and analyze risks, develop and apply risk management measures, summarize the results of the measures used, and prepare proposals.At the same time, mathematical algorithms specially developed by the author aimed at automatically determining the risk and its levels of understating or overstating the invoice value of imported goods presented by the participants of foreign economic activity for customs clearance are described.